Spatial Metadata: Guidelines and Procedures - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Spatial metadata or geographic metadata can be defined as metadata applicable to geographic data and information. This metadata can be stored along with geospatial data (vector and raster format) or may be listed in a separate document. There are many standards for geospatial metadata, including the International Organization for Standardization (ISO) and Federal Geographic Data Committee (FGDC) metadata standards. This document adopts (ISO) 19115-1:2014 – Geographic Information - Metadata as the standard for developing geographic information or spatial metadata.